Classification of Glioblastoma Based on Immunohistochemical Expression of IDH-1, p53, and ATRX: A Study from a Tertiary Care Center in South India - Thankayathil, Hiba; Govindan, Aparna; Kovilakam, Supriya Nilambur; Parambil, Rajeev Mandaka (Indian Journal of Neurosurgery, 2025)
Glioblastoma (GBM) is the most common malignant brain tumor in adults characterized by an extremely aggressive clinical phenotype. Understanding the molecular markers involved in GBM is critical for development of more effective and targeted therapies. The present study attempts to study the prevalence of immunohistochemical expression of IDH-1, p53, and ATRX in GBMs in our population.The present study is a descriptive cross-sectional study conducted in the department of pathology, on a total of 95 cases of GBM during the study period of 5 years. The immunohistochemical testing was done and evaluated.Out of 95 cases of GBM, 74 were IDH wild-type (IDH-1 − ) and 21 were IDH mutant (IDH-1 + ). In our study, 37.9% of cases showed p53 overexpression (p53 + ) and 46.3% of cases showed loss of ATRX expression (ATRX − ). A statistically significant association was found in the expression of p53 and ATRX among IDH mutant cases on combined three-protein analysis (p-value = 0.01). Majority of them were p53 negative (p53 − ) and showed ATRX loss. Among IDH wild-type cases, majority were negative for p53 with retained ATRX expression (ATRX + ), which was in concordance with other studies.These findings suggest that the identification of combinations of these protein markers may be useful for the classification and thus it may help to provide a deeper understanding of the molecular heterogeneity and aggressiveness of GBM and may help in the development of targeted therapies.
Keywords: ATRX; glioblastoma; IDH-1; immunohistochemistry; p53